RELATIONSHIP BETWEEN ATMOSPHERIC CO_2 AND CH_4 CONCENTRATIONS AT SYOWA STATION, ANTARCTICA - アオキ, シュウジ; ナカザワ, タカキヨ; ムラヤマ, ショウヘイ; シミズ, アキラ; ハヤシ, マサヒコ; イワイ, クニモト; AOKI, Shuhji; NAKAZAWA, Takakiyo; MURAYAMA, Shohei; SHIMIZU, Akira; HAYASHI, Masahiko; IWAI, Kunimoto (National Institute of Polar Research, 1994)
P(論文) Precise measurements of the atmospheric CO_2 and CH_4 concentrations have been continued at Syowa Station since 1984 and 1987,respectively. Measured concentrations show secular increase, together with seasonal cycle and irregular variations. Negative correlation is clearly seen between the secular trends of the CO_2 and CH_4 concentrations. The increase rates of CO_2 and CH_4 show oscillations with periods of 2.3 to 2.8 years. The phases of the average seasonal cycles of CO_2 and CH_4 coincide with each other, but interannual variations of the observed seasonal cycle of CO_2 are larger than those of CH_4 departmental bulletin paper